Development and Evaluation of a Positive Youth Development Course for University Students in Hong Kong - Shek, Daniel T. L. (The Scientific World Journal, 2012)
With higher education, university graduates are important elements of the labor force in knowledge-based economies. With reference to the mental health and developmental problems in university students, there is a need to review university's role in nurturing holistic development of students. Based on the positive youth development approach, it is argued that promoting intrapersonal competencies is an important strategy to facilitate holistic development of young people in Hong Kong. In The Hong Kong Polytechnic University, a course entitled Tomorrow's Leader focusing on positive youth development constructs to promote student well-being will be offered on a compulsory basis starting from 2012/13 academic year under the new undergraduate curriculum structure. The proposed course was piloted in 2010/11 school year. Different evaluation strategies, including objective outcome evaluation, subjective outcome evaluation, process evaluation, and qualitative evaluation, are being carried out to evaluate the developed course. Preliminary evaluation findings based on the piloting experience in 2010/11 academic year are presented in this paper.